"Better for women. Improving the health and wellbeing of girls and women" (2019) - Towards a women's health strategy for the UK. (20th October 2021) - Regan, L
Abstract: The following key questions will be addressed in the presentations: 1. What women's health issues are of particular concern in the report? 2. What is the data situation on important women's health topics in the UK, are there data gaps? 3. On which groups of women is there a particular focus in the report? 4. How can the findings be translated into policy? What has happened so far?